2022
DOI: 10.1051/epjconf/202225700036
|View full text |Cite
|
Sign up to set email alerts
|

The Three Hundred–NIKA2 Sunyaev–Zeldovich Large Program twin samples: Synthetic clusters to support real observations

Abstract: The simulation database of The Three Hundred Project has been used to pick synthetic clusters of galaxies with properties close to the observational targets of the NIKA2 camera Sunyaev–Zeldovich (SZ) Large Program. Cross–matching of cluster parameters such as mass and redshift of the cluster in the two databases has been implemented to generate the so–called twin samples for the Large Program. This SZ Large Program is observing a selection of galaxy clusters at intermediate and high redshift (0:5 < z < 0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Each of these is a unique representation of the LPSZ in the given criteria. The details of these TSs and their creations can be found in [11]. In this work, we use the simulated Compton parameter (y) maps and total project mass maps of the TSs.…”
Section: The300-nika2 Twin Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of these is a unique representation of the LPSZ in the given criteria. The details of these TSs and their creations can be found in [11]. In this work, we use the simulated Compton parameter (y) maps and total project mass maps of the TSs.…”
Section: The300-nika2 Twin Samplesmentioning
confidence: 99%
“…State-of-the-art N-body hydrodynamical simulations have been proven useful in increasing our theoretical understanding of such effects [10]. In this work, we deploy The300-NIKA2 twin samples (TSs) [11] to study the scatter induced on mass (M) and integrated SZ Compton parameter (Y) due to projection and construct 3D (Y − M) scaling laws at different ∆. We also investigate for the optimal overdensity at which the scatter due to the projection effect is minimised.…”
Section: Introductionmentioning
confidence: 99%
“…To address this situation better, recent observational studies have demonstrated the power of combining data from different facilities to probe a wide range of radial scales (Planck Collaboration et al 2013;Bartalucci et al 2017;Bourdin et al 2017;Romero et al 2017;Ghirardini et al 2019;Pointecouteau et al 2021), and such data are now becoming available for large samples with well-defined selections. In addition, mock observations of similarly selected samples from large volume simulations are increasingly being used for comparison in order to mitigate systematics related to analysis methods and population statistics (Gianfagna et al 2021;Paliwal et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…To better address this situation, recent observational studies have demonstrated the power of combining data from different facilities to probe a wide range of radial scales (Planck Collaboration et al 2013;Romero et al 2017;Bartalucci et al 2017;Bourdin et al 2017;Ghirardini et al 2019;Pointecouteau et al 2021), and such data are now becoming available for large samples with well defined selections. In addition, mock observations of similarly selected samples from large volume simulations are increasingly being used for comparison in order to mitigate systematics related to analysis methods and population statistics (Gianfagna et al 2021;Paliwal et al 2022).…”
Section: Introductionmentioning
confidence: 99%